2019
DOI: 10.1016/j.jmb.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Distinct Membrane Binding Activity of the Homologous C2A Domains of Myoferlin and Dysferlin

Abstract: Dysferlin has been implicated in acute membrane repair processes, whereas myoferlin's activity is maximal during the myoblast fusion stage of early skeletal muscle cell development. Both proteins are similar in size and domain structure; however, despite the overall similarity, myoferlin's known physiological functions do not overlap with those of dysferlin. Here we present for the first time the X-ray crystal structure of human myoferlin C2A to 1.9 Å resolution bound to two divalent cations, and compare its 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…Freeze-fracture electron microscopy has established that the number and structure of caveolae are changed in dystrophinopathy, suggesting an important role of abnormal cavins in muscular dystrophy [ 39 , 117 ]. Of note, the crucial repair protein myoferlin [ 118 ] is also closely associated with caveolin and intrinsically involved in the maintenance and structural integrity of the sarcolemmal membrane, together with the Ca 2+ -dependent repair protein dysferlin [ 119 ].…”
Section: Proteomic and Biochemical Characterization Of The Dystropmentioning
confidence: 99%
“…Freeze-fracture electron microscopy has established that the number and structure of caveolae are changed in dystrophinopathy, suggesting an important role of abnormal cavins in muscular dystrophy [ 39 , 117 ]. Of note, the crucial repair protein myoferlin [ 118 ] is also closely associated with caveolin and intrinsically involved in the maintenance and structural integrity of the sarcolemmal membrane, together with the Ca 2+ -dependent repair protein dysferlin [ 119 ].…”
Section: Proteomic and Biochemical Characterization Of The Dystropmentioning
confidence: 99%
“…However, despite laborious efforts from several research groups, this has not been the case for other C 2 domains so far, presumably because higher protein dynamics prevent the forming of crystals. Notably, the same seems to be true for the myoferlin and dysferlin C 2 domains, of which only the structures of the C 2 A domains could be resolved to date [ 61 ]. Whether the high flexibility of the ferlin C 2 B-C 2 F domains is a biological defect or a feature relevant for proper function remains to be determined.…”
Section: Localization and Presumed Effects Of Single Amino Acid Sumentioning
confidence: 99%
“…A recent publication confirmed that myoferlin and dysferlin C2A domains exhibit different Ca 2+ affinities. However, they describe myoferlin C2A domain with a lower Ca 2+ affinity than the dysferlin homolog C2 domain, and a marginal binding of myoferlin C2A domain to phospholipid mixture containing PS [33]. The binding of dysferlin C2A to PS was confirmed and extended to several phosphoinositide monophosphates in a Ca 2+ -dependent fashion.…”
Section: Ferlin’s Interactions With Phospholipidsmentioning
confidence: 99%